The German Protestant Churches and the World Council of Churches - Raiser, Konrad (The ecumenical review, 2022)
Against the background of the 11th Assembly of the World Council of Churches, to be held in Germany in 2022, this article reviews the history of the relationship between German Protestantism and the WCC from the mid-20th century to the present day. It recalls the relationship between the German Protestant Church and the ecumenical movement in the period of National Socialism, the new beginning that followed the Second World War, controversies over social and political involvement in the 1960s and subsequent decades, the existence of Protestantism in the two German states during the Cold War period, and subsequent efforts to promote justice, peace, and nonviolence.